Effectiveness of biosimilar pegfilgrastim in patients with lymphoma after high-dose chemotherapy and autologous stem cell transplantation: a real-life study - Loteta, Barbara; Pitino, Annalisa; Pitea, Martina; Alati, Caterina; Tripepi, Giovanni; Mico', Maria Caterina; Pellicano', Maria; Cogliandro, Francesca; Porto, Gaetana; Policastro, Giorgia; Utano, Giovanna; Delfino, Ilaria Maria; et al. (Frontiers in Hematology, 2024)
ObjectivesTo evaluate the efficacy of biosimilar (BIO) pegfilgrastim (PEG) in lymphoma patients after autologous stem cell transplantation (ASCT).Methods86 consecutive lymphoma patients who received BIO/PEG after ASCT were assessed. The primary endpoints of this study were the incidence of febrile neutropenia (FN) and time to neutrophil engraftment.ResultsMost patients were males (67.4%) with a median age of 48 years. FN occurred in 66 patients (76.7%), and most of the fever was grade 1-2. The median time to neutrophil engraftment was 9 days. The incidence of FN differs based on lymphoma type (p-value <0.01) and was higher in non-Hodgkin lymphoma (NHL) than in Hodgkin Lymphoma (HL). No statistical difference was found between NHL and HL regarding the time to reach the neutrophil engraftment. Hospitalization lasted from a minimum of 9 to a maximum of 34 days. The restricted mean time to discharge was 15.9 days (95%CI 14-16), without differences based on lymphoma type.ConclusionAlthough the study has the significant limitation of not being randomized and not having a control arm, it highlights the efficacy and safety of a BIO-PEG formulation in patients with Lymphoma and undergoing ASCT.